The Influence of Leadership Style and Motivation on Employee Performance at PTSL Bogor - Achmad Rozi; Umi Narimawati; Azhar Affandi; Sidik Priadana; Heri Erlangga (Peneliti.net, 2022)
This study aims to determine the effect of leadership style and motivation together on employee performance at PTSL Bogor. This research method uses quantitative methods with a causal research design (cause and effect). The population of this study were all employees of PTSL Bogor as many as 130 employees and the determination of the number of samples using saturated samples so that the number of samples was 99 respondents. The results of the t test, the value of t count is greater than t table (-1.043 > 1.985). so that Ho is accepted and Ha is rejected, that there can be no significant effect between leadership style on employee performance at PTSL Bogor. The results of the t test, the value of t arithmetic is greater than t table (9.105 > 1.985). So it can be concluded that H0 is rejected and Ha is accepted that there is a significant influence between work motivation on employee performance at PTSL Bogor. F test results of leadership style and motivation on Employee performance obtained F count > F table (61,846 > 3,091) and sig value F < (0.000 < 0.05).So it can be concluded that there is an effect of Leadership Style and Motivation together on Employee Performance. Leadership Style (X1) and Motivation (X2) affect employee performance simultaneously.